The Mediating Role of Placental Weight Change in the Association Between Prenatal Exposure to Thallium and Birth Weight: A Prospective Birth Cohort Study - Zhou, He; Sun, Xiaoli; Wang, Yiding; Ye, Yufeng; Chen, Hanwei; Chen, Qingsong; He, Guanhao; Wang, Jiaqi; Liu, Xin; Dong, Moran; Chen, Dengzhou; Chen, Guimin; et al. (Frontiers in Public Health, 2021)
Background: Previous studies have demonstrated the embryotoxicity and fetotoxicity of thallium (Tl). However, the effects of prenatal exposure to Tl on birth weight and placental weight and the mediating role of placental weight in the association of Tl with birth weight remain unclear. Methods: We recruited 2,748 participants from the ongoing Prenatal Environment and Offspring Health Cohort (PEOH Cohort) study, which was initiated in 2016 in Guangzhou, China. The Tl concentrations in maternal urine samples collected during the first and third trimester were determined by inductively coupled plasma mass spectrometry. Birth weight and placental weight were extracted from maternal medical records. Results: Pregnant women exposed to the highest tertile of Tl in the first trimester (β = −42.7 g, 95% CI: −82.3, −3.1 g) and third trimester (β = −50.6 g, 95% CI: −99.0, −2.3 g) had babies with lower birth weights than those exposed to the lowest tertile. We also found significant negative associations of exposure to Tl concentrations in the first and third trimester with placental weight. Mediation analyses showed that 50.3% (95% CI: 15.9, 79.2%) and 33.5% (95% CI: 1.3, 80.3%) of the effects of Tl exposure in the first and third trimester on birth weight were mediated by decreased placental weight. Conclusion: Our results suggest that prenatal exposure to Tl is negatively associated with birth weight and that this association may be mediated by decreased placental weight.